Paralogous Stellate and Su(Ste) repeats: evolution and ability to silence a reporter gene. - Gvozdev, V.A.; Kogan, G.L.; Tulin, A.A.; Aravin, A.A.; Naumova, N.M.; Shevelyov, Y.Y. (Genetica, 2000)
The X-linked Stellate repeats, encoding a putative regulatory subunit of protein kinase CK2, are expressed in XO male testes. The Y-linked, testes-expressed paralogous Su(Ste) repeats are thought to be suppressors of Stellate transcription. The unique, testis-expressed euchromatic gene was suggested to be an ancestor of the both types of amplified paralogous repeats. A Su(Ste)-like orphon was localized on a Y chromosome, outside of the Su(Ste) cluster. Several diagnostic molecular markers peculiar for the both types of diverged Stellate and Su(Ste) units were detected in the orphon sequence. The orphon was suggested to be a close relative of the immediate ancestor of both types of paralogous repeats which initiated evolution on the Y chromosome. Selection pressure on the level of translation was shown as a driving force in the evolution of Su(Ste) repeats, which are considered as more ancient derivatives of the ancestor euchromatic gene than Stellate repeats. In a vicinity of 12E Stellate cluster the undamaged, recently originated euchromatic Stellate orphon was found at 12D, providing the poly(A) signal for the bendless gene. P-element mediated transformations reveal that the fragments of cloned Stellate and Su(Ste) clusters are able to induce variegation of a reporter mini-white gene. The observed variegation phenomenon has peculiar features: a significant increase of trans-activation of a reporter mini-white gene in homozygous state; absence of effects of several conventional modifiers of position effect variegation (PEV) and independence of a severity of variegation on a distance between insertion and centromere region.